Ganti Rugi Terhadap Masyarakat Atas Kebakaran yang Disebabkan oleh Pencurian Energi Listrik Persfektif Wahbah Al-Zuhaili: Studi Kasus Desa Blangkejeren, Kecamatan Blangkejeren, Kabupaten Gayo Lues - Firmansyah Firmansyah; Rajin Sitepu (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
It cannot be denied that electrical energy has become a necessity in people's lives, almost all of people's daily activities are inseparable from the use of electrical energy. The existence of electrical energy facilities is sometimes not balanced with the development of the community's economy. Therefore, people often have difficulty meeting their daily needs with various activities that require electrical energy sources. So this is one of the factors why people try to obtain electrical energy supplies illegally. Of course, this is not only detrimental to PT. PLN is the electricity provider, but this also has a negative impact on society. Because the theft of electrical energy is carried out with minimal understanding and equipment, of course it does not meet the General Electrical Installation (PUIL) guidelines that apply in our country, so it has a low level of security and can cause various consequences, including changing the voltage up and down so that it can make the device - household electronic equipment is damaged, and can even cause fires which cause harm to many parties, both material and immaterial losses, as experienced by the people of Blangkejeren village. The aim of this research is to find out how the fire incident occurred which caused losses to the Blangkejeren community, and to find out how the compensation for the fire incident was carried out by the Blangkejeren community, as well as how the compensation was resolved by the Blangkejeren community from Wahbah al-Zuhaili's perspective. This research uses field research methods which are descriptive qualitative in nature. Data collection was carried out using interviews, observations and existing literature. From the research results, it was found that the people of Blangkejeren prioritize the elements of peace and harmony in solving the fire problem that occurred as a result of the theft of electrical energy. Based on the search results above, it can be concluded that the steps taken by the Blangkejeren community are appropriate in maintaining the traditional values ​​that apply in the community and are also in accordance with the ideas put forward by Wahbah al-Zuhaili.